2020
DOI: 10.4049/jimmunol.1901393
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Burn Injury Generates Bioactive Microvesicles: Evidence for a Novel Transport Mechanism for the Lipid Mediator Platelet-Activating Factor (PAF) That Involves Subcellular Particles and the PAF Receptor

Abstract: Thermal burn injuries are an important environmental stressor that can result in considerable morbidity and mortality. The exact mechanism by which an environmental stimulus to skin results in local and systemic effects is an area of active research. One potential mechanism to allow skin keratinocytes to disperse bioactive substances is via microvesicle particles, which are subcellular bodies released directly from cellular membranes. Our previous studies have indicated that thermal burn injury of the skin ker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 57 publications
1
37
0
Order By: Relevance
“…The biogenesis of MVP involves activation of the aSMase pathway, and previous reports including ours have shown that the inhibition of aSMase blocks MVP release regardless of the stimuli used [ 34 , 35 , 36 , 45 , 46 , 47 ]. To that end, our next studies tested the effect of a specific pharmacologic inhibitor of aSMase (i.e., imipramine) on targeted therapies-induced MVP release.…”
Section: Resultsmentioning
confidence: 57%
See 4 more Smart Citations
“…The biogenesis of MVP involves activation of the aSMase pathway, and previous reports including ours have shown that the inhibition of aSMase blocks MVP release regardless of the stimuli used [ 34 , 35 , 36 , 45 , 46 , 47 ]. To that end, our next studies tested the effect of a specific pharmacologic inhibitor of aSMase (i.e., imipramine) on targeted therapies-induced MVP release.…”
Section: Resultsmentioning
confidence: 57%
“…Given that gefitinib and erlotinib generate ROS in a process blocked by antioxidant and PAFR antagonist ( Figure 1 ), and our previous reports demonstrating that pro-oxidative stressors induce MVP release in a PAFR-dependent manner [ 34 , 35 , 36 ], we tested our working hypothesis if these targeted therapies can induce MVP release in lung cancer cells. It should be noted that depending upon the nature of the stimuli or the cell types, the secretion of MVPs has been shown to be time and/or concentration-dependent [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations